Complex scaling flows in quench dynamics of interacting particles - Enss, Tilman; Braatz, Noel Cuadra; Gori, Giacomo (Arxiv, 2022)
Many-body systems driven out of equilibrium can exhibit scaling flows of the quantum state. For a sudden quench to resonant interactions between particles we construct a new class of analytical scaling solutions for the time evolved wave function with a complex scale parameter. These solutions determine the exact dynamical scaling of observables such as the pair correlation function, the contact and the fidelity. We give explicit examples of the nonequilibrium dynamics for two trapped fermions or bosons quenched to unitarity, for ideal Bose polarons, and for resonantly interacting, Borromean three-body systems. These solutions reveal universal scaling properties of interacting many-body systems that arise from the buildup of correlations at short times after the quench.